A Genome-Wide Study of Allele-Specific Expression in Colorectal Cancer - Liu, Zhi; Dong, Xiao; Li, Yixue (Frontiers in Genetics, 2018)
Accumulating evidence from small-scale studies has suggested that allele-specific expression (ASE) plays important roles in tumor initiation and progression. However, few is known about genome-wide ASE in tumors. In this study, we conducted a comprehensive analysis of ASE in individuals with colorectal cancer (CRC) on a genome-wide scale. We identified 5.4 thousand genome-wide ASE of single nucleotide variations (SNVs) from tumor and normal tissues of 59 individuals with CRC. We observed Increased ASE level in tumor samples, and the ASEs enrich as hotspots on the genome, 63% of the genes located there were previously reported to be with complex regulatory elements, e.g., human leukocyte antigen (HLA), or implicated in tumor progression. Further focusing on the allelic expression of somatic mutations, we found that 37.5% of them exhibited ASE, and genes harboring such somatic mutations were enriched in important pathways implicated in cancers. In addition, by comparing the expected and observed ASE events in tumor samples, we identified 50 tumor specific ASEs which are possibly contributed by the somatic events in the regulatory regions of the genes and significantly enriched known cancer driver genes. By analyzing CRC ASEs from several perspectives, we provided a systematic understanding of how ASE is implicated in tumor and normal tissues, and will be of critical value in guiding ASE studies in cancer.